Формування експортного потенціалу підприємств зернової галузі - Чернявський, Іван Юрійович; Cherniavskyi, Ivan (Мелітополь : ТДАТУ, 2020)
UA: У дисертації розглянуто сутність економічної категорії «експортний потенціал» з урахуванням особливостей функціонування підприємств зернової галузі. Обґрунтовано теоретичні підходи щодо визначення ролі підприємства у системі міжнародної економічної діяльності з урахуванням концептуальних положень теорій і моделей міжнародної торгівлі сільськогосподарською продукцією. Узагальнено методичні засади, що характеризують рівень використання експортного потенціалу підприємств зернової галузі. Досліджено тенденції розвитку світового ринку зернових культур і проаналізувати конкурентні позиції України на міжнародних ринках пшениці, ячменю та кукурудзи. Здійснено діагностику сучасного стану функціонування підприємств зернової галузі України. Удосконалено організаційно-економічні засади формування експортного потенціалу підприємств зернової галузі з урахуванням динаміки зміни індексів відносних конкурентних переваг зерна кукурудзи на світовому ринку. Здійснено оцінку експортного потенціалу підприємств зернової галузі. Запропоновано перспективні напрямки нарощування обсягів виробництва кукурудзи в Україні та підвищення експортного потенціалу підприємств зернової галузі. Розроблено концептуальну модель стратегії розвитку та комплекс стратегій для вітчизняних підприємств зернової галузі, які спеціалізуються на вирощуванні кукурудзи на зерно. Здійснено прогнозування експортного потенціалу підприємств зернової галузі України з урахуванням рівня розвитку вітчизняної селекції на середньострокову перспективу. EN: The dissertation is devoted to research and substantiation of theoretical and methodological positions of identification and evaluation of export potential enterprises of grain industry and development of practical recommendations on the directions of its development. In this work the methods of estimation are investigated, as well as factors of development of export potential are analyzed. The paper researched the evolution of scientific thought in defining the concept of «potential», generalizes the views of domestic and foreign scientists on the interpretation of the content and components of the export potential of the enterprise, its place in the system of economic potential. It was established that the export potential of grain industry’s enterprises is the existing or potential capacity of the enterprise, which is determined by the set of its production, financial, personnel and marketing potentials under the influence of micro and macro factors of the business environment to carry out successful marketing activities in the global agri-food market. It is advisable to divide these elements of export potential into two blocks: block of resources (production and economic potentials) and block of competencies (quality of management system, organizational structure, microclimate in the team, relationships with partners, the level of marketing activities of seed enterprises). Research of export potential estimating methods made it possible to summarize and supplement their classification features: by the essence of potential, by the level of complexity, by the units of measurement, by the methods of evaluation, by the objects of evaluation, by the characteristics of the applied evaluation parameters. The domestic grain production development tendencies are substantiated; the peculiarities of organizing the Ukrainian corn grain export are analyzed. It was established that the main exporters of grain in Ukraine are agri holdings. They allocate significant funds to meet the needs of their own seed farms, which select elite seeds for the holding's agricultural enterprises’ needs, as well as sell it on the domestic market and abroad. In scientific work has been further developed the economic and mathematical modeling impact assessments on grain exports of the most important factors with defining the contributions of each of them in its dynamics, which allows forecasting grain exports and making reasonable management decisions regarding the formation and implementation the agricultural enterprises’ export potential. Based on correlation-regression analysis, the dependence of exports on the following factors was established, such as: the export price of corn grain, the export price of wheat grain and, accordingly, the volume of exports of corn and wheat by Ukraine, the ratio of world prices for these grains to domestic prices; gross grain harvest in Ukraine. The economic activity of one of the leading seed enterprises of Kyiv region, which is engaged in the selection of corn and winter wheat seeds – LLC “Agrofirma Kolos” is analyzed. The main activities of LLC “Agrofirma Kolos” are crop production, animal husbandry, processing of own production and scientific activity. The farm cultivates about 20 varieties of winter wheat and 15 hybrids of corn. The research has proved that domestic hybrids of corn seeds are highly productive, adapted to the natural and climatic conditions of Ukraine and have a yield potential from 12,5 to 15 t/ha. The assessment of the grain enterprises’ export potential shows that among the surveyed agricultural enterprises the highest level of export potential has LLC "Agrofirma Kolos", as the integrated indicator is 0.44, which is higher compared to other enterprises. Note, that the high value of this indicator is due to the higher level of production, economic, marketing and management potential. The lowest level of export potential has LLC “Lishchynske” – 0,307. It should be noted that despite the relatively high level of production potential, this company has much lower levels of usage the production and marketing potential. The results of the analysis of the Boston Consulting Group Matrix allow us to suggest the studied companies to choose the following development strategies. Thus, we offer LLC “Agrofirma Kolos” to choose a diversification strategy, LLC “Lishchynske” – an integration development strategy, State Enterprise “Experimental Farm Cherkaske“– an economic growth strategy based on innovations. Another direction of development the export potential of grain in Ukraine is defined the geographical diversification of its exports. One of the promising markets for corn grain for Ukrainian exporters with significant consumption potential is considered to be the following market: Egypt (in 2017/2018 MY the volume of production was at the level of 6 million tons with domestic consumption of 15,9 million tons); European Union - the Netherlands, Italy, Spain, Belgium (in 2017/2018 MY production was at the level of 60,091 million tons with domestic consumption of 64,931 million tons); Iran; Turkey; South Korea; Israel; Tunisia; South Africa and Jordan. The important condition for increasing exports is the compliance of grain with phytosanitary standards. It is concluded that an important influence on the formation and development of grain export potential has the institutional component, scilicet state regulation of the agricultural sector of Ukraine, which is considered as a set of methods, forms, tools and institutions to ensure sustainable development of the agricultural sector and the development of export potential, taking into account the comparative advantages of the country and the factors of globalization's development. The systematic approach’s application to the grain market regulation, the implementation of stable rules of economic activity is a necessary condition for the stable development of grain production and the development of its export potential. According to the average forecast in 2023, producers are able to export grain crops by 56,6 million tons, including corn – 32,3 million tons. Considering the risks in the production activities of agricultural producers and the uncertainty of economic processes in the future, were also proposed pessimistic and optimistic forecasts of grain exports, respectively, 52,1 and 60,1 million tons. Conceptual bases of increase the efficiency of an export potential’s formation process in agrarian formations on the basic of transition to bases of sustainable development, improvement of the management mechanism and the estimation order of the realization results of tools and actions are formed. It is proved that Ukraine's entry, as an equal partner on the international market, expansion of grain exports and further integration into the European marketing network, requires Ukrainian legislation to achieve equivalence with EU norms, and further constant confirmation of compliance with European and international standards. The main scientific conditions, which are substantiated in the dissertation, deepen the theoretical, methodical and practical knowledge on the issues of the economic potential enterprises’ formation of grain industry of Ukraine.
Formation of export potential of grain market’s enterprises
Keywords: експортний потенціал; підприємства зернової галузі; ринок зернових культур; організаційно-економічні засади; стратегія розвитку; прогнозування; export potential; grain market’s enterprises; grain market; organizational and economic principles; development strategy; forecasting